1976
DOI: 10.1128/iai.13.5.1343-1346.1976
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of classical and alternative pathways of human complement by "promptly serum-sensitive" and "delayed serum-sensitive" strains of Serratia marcescens

Abstract: Chelation of fresh human serum with 0.01 M MgCl, (Mg) plus 0.01 M ethylene glycol tetraacetic acid failed to abrogate the bactericidal activity against "delayed serum-sensitive" strains of Serratia marcescens, whereas previously "promptly serum-sensitive" strains of S. marcescens and control strain Escherichia coli C were killed after an extended period of incubation. The addition of 0.01 M ethylenediaminetetraacetate to fresh human serum neutralized bactericidal activity against S. marcescens of either serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…The majority of isolates were able to resist complement attack at a serum concentration of 50%. This is comparable with previously published results (25,26). The ability to resist complement may allow the bacteria to remain in the closed-eye environment, where complement is present at a concentration of 2 -15%.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of isolates were able to resist complement attack at a serum concentration of 50%. This is comparable with previously published results (25,26). The ability to resist complement may allow the bacteria to remain in the closed-eye environment, where complement is present at a concentration of 2 -15%.…”
Section: Discussionsupporting
confidence: 92%
“…This shows that the serum sensidvity among strains within a species could \'ary. Different degrees of sensitivity to the bactericidal acdvity of serum have been nodced among strains of the same species for a variety of other gram-negadvehacteria (5,14,21,27,30,42). It is not known, however, why different strains show different degrees of sensidvity (2,26).…”
Section: Discussionmentioning
confidence: 99%
“…Serum was either heat inactivated (open symbols) or active (closed Moreover, the definitions of serum resistance and susceptibility depend upon the techniques chosen to monitor the reaction (1, 3, 4, 6, 9, 12, 16, 21, 24-28, 36-38, 40). Most of these methods are based on viable counts (1,4,6,16,28,32,(34)(35)(36); on the measurement of metabolic pertubations (22,34), cell respiration (18,33), or the release of various cell products, such as enzymes (20,32,33), DNA (2), radiolabeled thymidine (21,27), labeled ions (34), or 51Cr (13,30,34); or on photometric growth assays (24,32,39). It has been previously demonstrated that bacteriolysis represents the conversion of spheroplasts to ghost cells (8).…”
Section: Discussionmentioning
confidence: 99%